Dilema iman dalam mencari kesembuhan dari praktik pengobatan ke dukun di desa gunung bayu, kecamatan silou kahean, kabupaten simalungun - Lusyana Putri Purba; Pardomuan Munthe (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
This study was motivated by the faith dilemma experienced by the people of Gunung Bayu Village who have embraced the Christian faith, yet continue to seek healing through shamanistic practices despite acknowledging God as the sole source of healing. This practice creates tension between Christian teachings and local cultural traditions. The objective of this study is to provide a dogmatic review of Christian congregants who seek healing through shamanistic practices, as well as to examine the faith understanding of the people of Gunung Bayu Village regarding the doctrine of God as the only source of healing, using a qualitative approach with descriptive-dogmatic analysis. The findings indicate that seeking healing through shamanistic practices contradicts the Christian faith because it reflects dependence on powers other than God and involves elements of syncretism. Based on these findings, it is concluded that the church needs to strengthen theological teaching, pastoral care, and holistic ministry that is relevant to the spiritual struggles of the community.